Firms and inequality in Latin America - Marcela Eslava; Marcela Meléndez Arjona; Gabriel Ulyssea; Nicolás Urdaneta; Ignacio Flores (Inter-American Development Bank (IDB), 2024)
The relationship between firms and inequality has been a focus of recent attention globally. This chapter summarizes basic facts about this relationship for Latin America. Unlike advanced economies where superstar firm growth has prompted concerns over disproportionate income growth at the top, the facts we summarize illustrate that the main concern for Latin America is the extreme prevalence of tiny businesses whose workers and owners tend to populate the bottom income segments. The empirical likelihood that these businesses improve their productivity and grow to hire more workers and pay better wages is also very low. The region displays a deficit of employment generation in SMEs, by contrast to both microbusinesses (including self-employment) and large corporations. While the former tend to remunerate both workers and owners with very low incomes, the latter pay high wages but also exhibit low labor shares.
Keywords: E2; J21; O54; 330; Inequality; Business Development; Latin America; Labor Force and Employment; Betriebsgröße; Unternehmenswachstum; Einkommensverteilung; Brasilien; Mexiko; Lateinamerika